Pendidikan sejarah Islam Asia Tenggara: overview penyebaran Islam melalui Bibliometrik - Suhaimi Suhaimi; Muhammad Resqi; Ifdil Ifdil; Darmawati Darmawati; Istiqomah Istiqomah; M. Fahli Zatrahadi (Jurnal Konseling dan Pendidikan, 2022)
This study examines the most relevant themes related to the spread of Islam through bibliometric analysis using the keyword "spread of Islam" as input to obtain a comprehensive understanding of the spread of Islam and understand the current concentration of research. Since Scopus is considered the best source for bibliometric analysis, it is used. As a bibliometric analysis tool, VOSviewer software was chosen to visualize author networks, countries, journals, and keywords. A total of 161 documents from 1911 to 2022 were found through research conducted on October 29, 2022. The results showed that the topic of the spread of Islam from year to year still experienced ups and downs in its publications. However, the theme of the spread of Islam has now developed and is in demand by researchers. Currently the United State is the most prominent country in publications. while Bonner M. has the most articles and citations of any author. The Russian Academy of Sciences is the institution with the highest number of publications. while the journals that publish the most about the spread of Islam are the University of Oxford United Kingdom and the Institute of History and Philo Taiwan. The bibliometric studies offered offer relevant information on the main themes studied regarding the global spread of Islam.